Relative transcript abundance in porcine cumulus cells collected from different sized follicles. Issue 2 (23rd December 2020) - Moros‐Nicolás, Carla; Izquierdo‐Rico, Mª José; Li, Yang; González‐Brusi, Leopoldo; Romar, Raquel; Funahashi, Hiroaki
Abstract: Crosstalk between the oocyte and surrounding cumulus cells (CCs) is essential for the production of competent oocytes. Previous studies have analysed the relative transcript abundance in oocytes derived from small (SF: <3 mm diameter)‐ and medium‐sized (MF: 3–6 mm diameter) follicles to determine the potential use of SF‐derived oocytes in assisted reproductive technologies (ART). The aim of this study was to examine the relative transcript abundance of CCs obtained from cumulus–oocyte complexes (COCs) derived from SF and MF. Nine genes were selected according to their importance for developmental competence: AT‐rich interaction domain 1B (ARID1B), bone morphogenic protein receptor 2 (BMPR2), CD44, follicle‐stimulating hormone receptor (FSHR), follistatin (FST), inhibin beta‐A (INHBA), luteinizing hormone receptor (LHR), nuclear receptor subfamily 2 group F member 6 (NR2F6) and vascular endothelial growth factor A (VEGFA). The expression of these genes was analysed by RT‐qPCR. The results pointed to significant differences in five genes, and the relative transcript abundance of SF‐derived CCs was lower in the case of INHBA, but higher in FSHR, FST, LHR and NR2F6 compared with MF‐derived CCs. We provide information of gene activity in the porcine CCs from different sized follicles, thus improving our understanding of oocyte biology and providing new markers that identify viable and competent oocytes.